Hubungan Tingkat Kecemasan peserta dan Frekuensi Keikutsertaan Uji Kompetensi dengan Hasil Uji Kompetensi Bidan Nasional (UKBI) di Sulawesi Selatan Periode Juli-September 2020 - Ferawati Taherong; Anieq Mumthi’ah Alkautzar (POLTEKKES KEMENKES MANADO, 2021)
Background: The passing rate of the competency test is one of the parameters to assess the level of efficiency and effectiveness of the teaching and learning process of an educational institution. The achievement of passing the competency test is influenced by several factors, both internal and external. Internal factors that significantly affect the results of the competency test of graduates are intelligence, psychological condition (anxiety), physical condition, test readiness and learning achievement. Purpose: this study was to determine the relationship between the level of anxiety and the frequency of participant participation with the results of the Indonesian midwife competency test. Method: This type of analytic survey research with a cross sectional study approach using the snowball sampling technique with a sample size of 192 respondents. Results: There is a significant relationship between the level of anxiety and the results of the competency test with a value of P = 0.000 (<α value), there is a significant relationship between the frequency of participant participation and the results of the competency test with a value of P = 0.000 (<α value). The higher the level of anxiety and the more often you take the competency test, the greater the failure rate of the graduate competency test. Further research is needed on how to compare the level of anxiety between the firstaker and the retaker against the Indonesian Midwife Competency Test. Keyword : Competency Test, Anxiety